Childhood pneumonia in New Zealand. (4th March 2022) - Loto‐Aso, Eseta; Howie, Stephen RC; Grant, Cameron C
Abstract : While deaths from pneumonia during childhood in New Zealand (NZ) are now infrequent, childhood pneumonia remains a significant cause of morbidity. In this viewpoint, we describe pneumonia epidemiology in NZ and identify modifiable risk factors. During recent decades, pneumonia hospitalisation rates decreased, attributable in part to inclusion of pneumococcal conjugate vaccine in NZ's immunisation schedule. Irrespective of these decreases, pneumonia hospitalisation rates are four times higher for Pacific and 60% higher for Māori compared with children of other ethnic groups. Consistent with other developed countries, hospitalisation rates for pneumonia with pleural empyema increased in NZ during the 2000s. Numerous factors contribute to childhood pneumonia acquisition, hospitalisation and morbidity in NZ include poor quality living environments, malnutrition during pregnancy and early childhood, incomplete and delayed vaccination during pregnancy and childhood and variable primary and secondary care management. To reduce childhood pneumonia disease burden, interventions should focus on addressing modifiable risk factors for pneumonia. These include using non‐polluting forms of household heating; decreasing cigarette smoke exposure; reducing household acute respiratory infection transmission; improving dietary nutritional content and nutrition during pregnancy and early childhood; breastfeeding promotion; vaccination during pregnancy and childhood and improving the quality of and decreasing the variance in primary and secondary care management of pneumonia.